The Diversity of School Social Work in Germany: A Systematic Review of the Literature - Kathrin F. Beck (International Journal of School Social Work, 2017)
Children in Germany are confronted with an increasing societal inequality and disorientation that makes it difficult for them to cope with life. School social work in Germany is an intensive form of cooperation between the institutionally divided systems of child and youth welfare and education. The aim of this article is threefold: to present (1) relevant aspects of both systems, (2) the diversity of terms being used to describe this specific form of cooperation and (3) an exemplary selection of concepts of school social work. Therefore, a systematic review of the literature was done, taking publications between 2000 and 2016 into account. The findings show that there is a high diversity of terms being used to describe this form of cooperation as well as different concepts which have some similarities and differences. Therefore, school social work in Germany must be characterized as diverse, incoherent and in need of further clarification.
Keywords: School Social Work; International School Social Work; Germany; Child Welfare; Legal Bases; Education; Youth Welfare; Concepts